(3bWYI ef CeGdi bGVi GdbVGI YHO GdLHGQ Hf CMeO GdgeOGfis - (3YHO GdLHGQ Hf CMeO GdgeOGfj,J (B415 (3g` s
(3ChdgG (B:s
(3CNHQfG GdbGVi CHh eMeO YWjI CNHQfG HESfGO dg jQaYg Edi CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hYfg HESfGOg Edi GdeZjQI Hf TYHI bhdg (B: (3ceG jaYd efcQ fYeg Ydi gPG GdhLg Je Pdc hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3cJHJ GdYfGhjjf HGdMeQIs
(3HChQGbgG CKQ JbUas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdJhMjO hGdedd hGdfMds